2022
DOI: 10.1002/ps.6911
|View full text |Cite
|
Sign up to set email alerts
|

Novel insecticidal 1,6‐dihydro‐6‐iminopyridazine derivatives as competitive antagonists of insect RDL GABA receptors

Abstract: BACKGROUND: The ionotropic γ-aminobutyric acid (GABA) receptor (iGABAR) is an important target for insecticides and parasiticides. Our previous studies showed that competitive antagonists (CAs) of insect iGABARs have the potential to be used for developing novel insecticides and that the structural modification of gabazine (a representative CA of mammalian iGABARs) could lead to the identification of novel CAs of insect iGABARs.RESULTS: In the present study, a novel series of 1,3-di-and 1,3,5-trisubstituted 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…[13][14][15] After many years of insect GABAR research, it has been confirmed that (i) the amino acid sequences of RDLs have a high degree of similarity to those of mammalian GABA A R subunits, (ii) the RDL subunit can form a functional, homomeric GABA-gated chloride channel that pharmacologically resembles native insect GABARs, and (iii) the insect GABARs composed of RDL subunits (RDLRs) constitute a relevant target for insecticides. 16 However, the research into insect GABARs lies behind that of mammalian GABARs, particularly in mechanistic aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] After many years of insect GABAR research, it has been confirmed that (i) the amino acid sequences of RDLs have a high degree of similarity to those of mammalian GABA A R subunits, (ii) the RDL subunit can form a functional, homomeric GABA-gated chloride channel that pharmacologically resembles native insect GABARs, and (iii) the insect GABARs composed of RDL subunits (RDLRs) constitute a relevant target for insecticides. 16 However, the research into insect GABARs lies behind that of mammalian GABARs, particularly in mechanistic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Four subunits or subunit‐like proteins of insect ionic GABARs are known to date in various insects: RDL Resistance to dieldrin (RDL), GABA and glycine‐like receptor of Drosophila (GRD), Ligand‐gated chloride channel homolog 3 (LCCH3), and Dmel/CG8916 orthologs 13–15 . After many years of insect GABAR research, it has been confirmed that (i) the amino acid sequences of RDLs have a high degree of similarity to those of mammalian GABA A R subunits, (ii) the RDL subunit can form a functional, homomeric GABA‐gated chloride channel that pharmacologically resembles native insect GABARs, and (iii) the insect GABARs composed of RDL subunits (RDLRs) constitute a relevant target for insecticides 16 . However, the research into insect GABARs lies behind that of mammalian GABARs, particularly in mechanistic aspects.…”
Section: Introductionmentioning
confidence: 99%